Análise cladística e revisão taxonômica de Tobias Simon, 1895 (Araneae, Thomisidae, Stephanopinae) - Silva, Miguel Machado da (2016)
Since the original proposition of Thomisidae, much has been discussed about its taxonomy and intra-family relations. The subfamily Stephanopinae comprises individuals characterized by the presence of cheliceral teeth and by the anterior legs stronger and larger than the posterior ones, however, the monophyly of this group has not been corroborated due their dubious diagnostic characters and by the lack of revisional studies on several of its component genera. A phylogenetic analysis followed by a morphological revision of the spider genus Tobias Simon, 1895 are performed. The analysis is based on a matrix with 29 terminal taxa (7 in ingroup and 22 in outgroup) scored for 87 morphological characters. The implied weighting analysis resulted in one most parcimonious tree with 294 steps obtained in 16 distortion groups, which support that Tobias is paraphyletic with Epicadus Simon, 1895, and considered its junior synonym. Onocolus Simon, 1895 emerge as the sister group of Epicadus. Epicadus pulcher Mello-Leitão, 1929 comb. nov. is considered senior synonym of Epicadus epicadoides Mello-Leitão comb. nov., 1944 and Epicadus regius Birabén, 1955 comb. nov., Epicadus granulatus Banks, 1909 is proposed as senior synonym of Epicadus inermis Mello-Leitão, 1929 comb. nov., Epicadus camelinus (O. Pickard-Cambridge, 1869) comb. nov. is considered senior synonym of Epicadus martinezi Birabén, 1955 comb. nov. and Epicadus trituberculatus (Taczanowski, 1872) comb. nov. is considered senior synonym of Epicadus paraguayensis Mello-Leitão, 1929 comb. nov. and Epicadus planus Mello-Leitão, 1932. New distribution records and redescriptions are provided. The species latter described in Tobias, Epicadus caudatus Mello-Leitão, 1929 comb. nov., Epicadus pustulosus Mello-Leitão comb. nov., 1929, and also the original species Epicadus heterogaster (Guérin, 1829) and Epicadus rubripes Mello-Leitão, 1924 were recently revised, thus, they were not described in the present study. After the cladistics analysis, Epicadus now comprises 9 species.